Keteladanan Guru Pendidikan Agama Islam dalam Pembentukan Karakter Religius Siswa Madrasah Tsanawiyah - Intan Ayu Sukmawati; Poppy Rachman; Mohamad Solihin (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the role of Islamic Religious Education (IRE) teachers as role models in the process of internalising religious character among students at MTs al-Islamiyah Krejengan, Probolinggo. A qualitative approach was employed, specifically a case study. Data collection was carried out through observation, in-depth interviews, and documentation. The results of the study indicate that PAI teachers play a strategic role as role models (uswah hasanah) through the consistency of their attitudes, speech, and daily religious behaviour. Internalisation strategies include direct role modelling, the cultivation of religious practices, moral reinforcement, and the creation of a religious culture within the madrasah. Of the 116 students, approximately 90% actively participated in religious activities and 80% demonstrated good religious behaviour. Supporting factors included the boarding school environment and structured habit-forming programmes, whilst inhibiting factors included differences in student character and a lack of awareness among some students regarding the consistent application of religious values. This study confirms that the exemplary conduct of Islamic Education teachers is a key factor in effectively and sustainably shaping students’ religious character. Furthermore, the success of internalising religious character is also influenced by cooperation between teachers, the madrasah administration, and the family environment in fostering positive habits among students